Value capture dynamics – opportunity-driven changes - Najda-Janoszka, Marta (Contemporary organisation and management. Challenges and trends, 2020)
The study addresses the gap in the research concerning the dynamics of the value capture process. The aim is to enhance the understanding of the dynamics of value appropriation by identifying those decision-making practices and strategic behaviours that are entrepreneurial in nature. The conceptual discussion is supported by the empirical research governed by a multiple case design. The longitudinal study generated valuable insights into the processual character of value appropriation, as well as into its variable, not always linear, occurrence with value creation. The collected data provide rich evidence of opportunity-driven changes in the value capture action lines.